ANALISIS EFEKTIVITAS DAN EFISIENSI PENGELOLAAN PIUTANG PADA EMERALD HOTEL TIMIKA - Ahmad Tomu; Tika Irmawati Ishak (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2022)
This study aims to determine the level of receivables turnover, the average day of collection of receivables, as well as the performance of receivables based on receivable collection activities conducted by Emerald Hotel Timika. This research is a descriptive study with data collection techniques using observation, interviews and documentation. The data analysis instrument used in this research is the analysis of the receivables turnover rate, the average days of collection of receivables, the ratio of arrears and the ratio of collections. The results of the analysis show that the overall receivables turnover rate at Emerald Hotel Timika can be said to be very effective, although there is a decline in 2020, this can be proven by a significant increase in 2021. The average days receivable collection at Emerald Hotel Timika is very good. so that the collection of receivables can be said to be very efficient. Billing activity at Emerald Hotel Timika seen from the ratio of arrears and billing ratio can be concluded that the billing activity at Emerald Hotel Timika is quite good.